Surgical management of a delayed post‐traumatic saccular aneurysm of the radial artery. Issue 7 (24th July 2021) - Chalidis, Byron; Kitridis, Dimitrios; Tirta, Maria; Galanis, Nikiforos; Givissis, Panagiotis
Abstract: Post‐traumatic aneurysm of the radial artery is a rare and often misdiagnosed vascular lesion of the wrist. Radial artery ligation can lead to excellent results if Allen test confirmed that ulnar artery is the dominant feeding artery to the hand. Abstract : Post‐traumatic aneurysm of the radial artery is a rare and often misdiagnosed vascular lesion of the wrist. Radial artery ligation can lead to excellent results if Allen test confirmed that ulnar artery is the dominant feeding artery to the hand.